Evaluation in vitro of insecticides for control biorational Agrotis ipsilon hufnagel - Jojoa Bravo, Carolina Jasmin; Salazar González, Claudia (Revista de Ciencias Agrícolas, 2011)
The experiment was conducted in the laboratory of entomology at the University of Nariño. We evaluated the efficacy of products and chemicals biorracionales control Agrotis ipsilon in laboratory conditions. By using a random unreservedly factorial arrangement where the factor A found in the treatments: T1 Micosplag® (Metarhizium anisopliae, Paecilomyces lilacinus, beauveria bassiana), T2 Bassianil® (Beauveria bassiana), T3 Metabiol® (Metarhizium anisopliae), T4 Turilav® (Bacillus thuringiensis), T5 Alisin® (garlic-chili), T6 Lorsban® (chlorpyrifos) and T7 absolute control (distilled water), and factor B corresponded to the second and fourth larval instar. Chlorpyrifos had the highest mortality rate in contrast to other treatments in instars 2 and 4 in the two periods of evaluation, 48 hours and 8 days, finding statistically significant differences with respect to other products evaluated. Of note is the percentage of mortality obtained by applying the treatment 5 (Alisin ® in the instar 2 to 48 hours of evaluation with an efficiency of 22.64%. Furthermore, in the third period of evaluation after 8 days to apply the treatment 4 (Turilav ®) showed an efficiency of 33.96% and 38.66% in instar 2 and 4 respectively in both states presenting statistically significant differences compared to other treatments.